2016
DOI: 10.3126/ijosh.v4i2.12544
|View full text |Cite
|
Sign up to set email alerts
|

Noise Induced Hearing Loss in Steel Factory Workers

Abstract: Abstract:Background: Industrial noise is usually considered mainly from the point of view of environmental health and safety, rather than nuisance, as sustained exposure can cause permanent hearing damage. Objective: To assess the Noise induced hearing loss in steel factory workers. Methods: It was a cross sectional study done to evaluate the hearing status of factory workers, working nearby a rural hospital, which were then correlated with the duration of work and SPL (in dBA) of exposure at their workplace. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 34 publications
2
7
0
1
Order By: Relevance
“…In Nepal, the prevalence among workers in a steel factory was comparable to our study, i.e., 40% and 46% for the right and left ear, respectively. However, the study excluded workers over 45 years and information on factory characteristics were not available [35]. Another study done in Nepal among 115 small-scale metal industry workers and 123 controls found lower prevalence for the exposed (30%) and only 4% for the controls [36].…”
Section: Discussionmentioning
confidence: 99%
“…In Nepal, the prevalence among workers in a steel factory was comparable to our study, i.e., 40% and 46% for the right and left ear, respectively. However, the study excluded workers over 45 years and information on factory characteristics were not available [35]. Another study done in Nepal among 115 small-scale metal industry workers and 123 controls found lower prevalence for the exposed (30%) and only 4% for the controls [36].…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, workplace noise is regarded as a hazard linked to heavy industries such as the steel industry and associated with noise-induced hearing loss (NIHL). Currently, in terms of occupational health and safety, it is accepted that noise is hazardous to workers’ health in many areas of employment and by different means 1,2. Occupational NIHL is irreversible, and prevention, even in the early stages, is of the utmost importance 3…”
Section: Introductionmentioning
confidence: 99%
“…Currently, in terms of occupational health and safety, it is accepted that noise is hazardous to workers’ health in many areas of employment and by different means. 1 , 2 Occupational NIHL is irreversible, and prevention, even in the early stages, is of the utmost importance. 3 …”
Section: Introductionmentioning
confidence: 99%
“…The results of their studies show, that 235 employees were exposed to the noise for 16 to 20 years time. Among the employees with such job seniority 7 had medium hearing loss diagnosed in a right ear, while 8 in a left ear (25). A small number of diagnosed cases of hearing loss for women results from the fact, that the a/m occupational illnesses appears in sections and activities of PKD (Polish Activity Classification) where majority of the working staff are men.…”
Section: Discussionmentioning
confidence: 99%
“…Z ich badania wynika, że 235 pracowników było narażonych na hałas przez okres czasu od 16 do 20 lat. Wśród pracowników z takim stażem pracy u 7 stwierdzono umiarkowaną utratę słuchu w uchu prawym, natomiast w uchu lewym u 8 (25).…”
Section: Discussionunclassified